Teoria dos ciclos econômicos: o caso brasileiro entre 2003 e 2018 - Vaz-Curado, Samuel Fernandes Lucena (2019)
The economic cycle is one of the main fields of economic science. This dissertation discusses cycle theories of Keynesian and Austrian orientations. According to Keynesian economists, cycles are a consequence of fluctuations in confidence and expectations and must be answered by countercyclical economic policies. To develop this current, one draws on Keynes's original contributions, the ISLM model, and post-Keynesian considerations on the cycle. For Austrian economists, short-term fluctuations are natural, but the economic cycle is caused by imbalances in the money market and the price system. As a development of the Austrian theory, the dissertation makes an exposition of the GSMS model. The empirical analysis approaches the Brazilian economy between 2003 and 2018. Despite high growth rates at first, the economy arrives at the last years of the 2010 stagnated, without being able to increase its production and with a high number of unemployed. The objective is to relate the increase of credit and currency during the period proposed with the phases of economic expansion and retraction, in the context of the inflation targeting system. The dissertation proposes the investigation of the motivations behind the macroeconomic policies, seeking to identify the official opinion of the government. Therefore, it is proposed to read the minutes of Copom meetings and relevant speeches and laws throughout the period. In addition, bibliographic review and descriptive statistics are used. The dissertation indicates points of agreement between Austrians and Keynesians, such as the excess of unsubstantiated investments in the high phase of the cycle and the thesis of non-neutrality of money. The empirical results indicate that the Copom, following the inflation targeting system, ignored the excessive growth of the money supply.